PERANAN ISTRI PETANI DALAM MENINGKATKAN KESEJAHTERAAN RUMAH TANGGA - Hartiwi Agustina (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The farmer-wives have a vital role in coping and resolving their families’ poverty. The role itself is still cannot be separated with the stereotypical concept of an ideal woman figure among Indonesian society which later determines the farm work they are allowed to engage with. This study was set in two objectives, namely (1) to find and investigate the kind of role the farmer-wives engage on domestic sector in the effort of increasing their domestic welfare and (2) to find and investigate the farmer-wives’ role in public sector to increase their domestic welfare. Thereof, the descriptive research method was implemented in this study to give a broad description and explanation according to the data and information collected about the role of farmer-wives in increasing the domestic welfare of their families. The results of this study showed that (1) in accordance to the 12 correspondents, either direct or indirectly the farmer-wives have a vital role in increasing the domestic welfare of their families, (2) the role of housewives in the domestic life is relatively dominant according to the general tasks they work on, (3) farmer-wives directly and indirectly contribute in the farm work for they are active workers with particular tasks in the farm along with the side-job they are put on proposed by their spouses, and (4) farmer-wives in general have a side job as an effort to enhance the domestic welfare of their families.